Record and Appraisal of Endophytic Tumor Localization Techniques in Minimally Invasive Kidney-Sparing Procedures. A Systematic Review - Paparidis, Spyridon; Spartalis, Eleftherios; Mavrigiannaki, Eleftheria; Ferakis, Nikolaos; Stravodimos, Konstantinos; Tsourouflis, Gerasimos; Dimitroulis, Dimitrios; Nikiteas, Nikolaos I. (Urology Journal, 2022)
Purpose: Review and efficacy assessment of techniques used for intraprocedural endophytic renal mass localization. Materials and Methods: Advanced search was carried out on PubMed, Cochrane Library, Web of Science and Google Scholar databases up to August 2020. Eligibility criteria were set, according to PRISMA statement. OR (95 % CI) for identification or technical success, positive margins and recurrence, were calculated for completely endophytic tumors. Risk of Bias was evaluated using ROBVIS tool. Results: 77 studies used for result synthesis, including 1,317 endophytic tumors, with 758 of them completely endophytic. 356 endophytic tumors treated laparoscopically and 598 robotically, using ultrasound-based methods, transarterial embolization, dual-source CT, invasive signage, 3D printing, and augmented reality variations. Identification success was 97.8-100%, positive margins 0-12.5 % (completely endophytic: 95 % CI; 0.255-1.971, OR 0.709 in laparoscopic, 95 % CI ; 0.379-3.109, OR 0.086 in robotic partial nephrectomy), recurrences 0-3.9 % (completely endophytic: 0 recurrences in laparoscopic, 95 % CI ; 0.0917-2.25, OR 0.454, in robotic partial nephrectomy), and complications 0-60 % . 363 were treated with ablation techniques using CT-based methods, thermal monitoring, transarterial embolization, ultrasound guidance and invasive signage. Technical success was 33.4-100 % (completely endophytic: 95 % CI ; 0.00157-2.060, OR 0.0569 for invasive and 95 % CI ; 0.598-13.152, OR 2.804 for non-invasive localization techniques) and recurrences were 0-20%. Conclusion: Ultrasound-based techniques showed acceptable identification success and oncologic outcomes in laparoscopic or robotic setting. Augmented reality, showed no superiority over conventional techniques. Near infrared fluoroscopy with intravenous indocyanine green, was incapable of endophytic tumor tracking, although when administered angiographic, results were promising, along with other embolization techniques. Percutaneous hook-wire or embolization coil signage, aided in safe and successful tracking of parenchymal isoechoic masses, but data are inadequate to assess efficacy. CT-guidance, combined with ultrasound or thermal monitoring, showed increased technical success during thermal ablation, unlike ultrasound guidance that showed poor outcomes.